A Magnetic Tracking System Featuring Calibrated Three-Axis AMR Sensors - Thomas Quirin; Corentin Féry; Céline Vergne; Morgan Madec; Luc Hébrard; Joris Pascal (Proceedings)
This article presents a magnetic tracking system using on-chip anisotropic magnetoresistive (AMR) sensors. The system consists of four air-core coils sequentially generating four dc magnetic fields. The implemented localization algorithm is quadrilateration, and the accuracy of the system is dependent on the accuracy of the sensors and the simulated field maps. The performance of the system was evaluated using an in-house magnetic field camera (MFC), and the results showed that the system exhibits mean Euclidean errors below 1 mm where the source produces strong gradients. Given the dimensions of the sensors (0.82 × 0.82 mm2), this system is suitable for tracking minimally invasive surgical tools.